Strengthening Character Education for Elementary School Children through Rugby Games - Widianto, Rahmat Tri; Suherman, Ayi; Supriyadi, Tedi (Department of Physical Education, Sport, Health and Recreation, 2023)
Physical education has a special responsibility to strengthen the character of learners. The game of Rugby is one of the sports that is expected to be able to instill character values that prioritize integrity and solid Cooperation in everything to achieve success. This study explores the strengthening of character education for learners through rugby games. This study used a case study design involving 15 students and 1 physical education teacher in one elementary school in the Sumedang Regency, West Java, Indonesia. Data collection was carried out by distributing questionnaires with short answers followed by semi-structured interviews with 1 participant. This study explores five indicators of strengthening character education: religious character, nationalism character, independent character, mutual aid character, and integrity character. This research contributes to the improvement of character education of students in elementary schools through rugby games. In addition, this research can guide teachers or academics in developing research on students' character within the framework of character education